Kisah Cinta Tidak Indah : Studi Kekerasan dalam Relasi Pacaran Mahasiswa di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Cenderawasih Jayapura - Fitrine Christianne Abidjulu; Rima Nusantriani Banurea (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
Dating is a popular relationship among college students. In our expectation, dating becomespopular because it is fun. However, in reality, dating is tend to be unpleasure relationship.This can be occured because of violence. The existence of violence in dating has a strongrelation with the understanding of love. Love is often misunderstood by people who aredating as a ownership and control. Therefore, the topic about how violence’s manifest indating relationships is important question. This research aims to look the relationshipbetween college students in Faculty of Social and Political Sciences (FISIP) ofCenderawasih University, Jayapura, Papua. The results of this study are the concept of loveare important to building (consciously or unconsciously) violent acts in dating relation.Then the culture and experience from both the victims and the perpretators are important toperpetuating violence. Furthermore, the general form of violence at least exists in 5 formslike psychological violence, physical violence, verbal violence, digital violence and financialviolence.